The Risk Management of Minimum Return Guarantees - Antje Mahayni; Erik Schlögl (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
We analyse contracts which pay out a guaranteed minimum rate of return and a fraction of a positive excess rate, which is specified on the basis of a benchmark portfolio. These contracts are closely related to unit–linked life–insurance/savings plan products and can be considered as alternatives to a direct investment in the underlying benchmark portfolio. The option embedded into the savings plan is in fact a power option, and thus the specification of the ``fair'' contract parameters is closely related to well known features of these financial derivatives. The key issue, both in order to rigorously justify valuation by arbitrage arguments and to prevent the guarantees from becoming uncontrollable liabilities to the issuer, is the risk management of the embedded options by a tractable and realistic hedging strategy. The long maturity of life–insurance products makes it necessary to lift the Black/Scholes assumptions and consider an uncertain volatility scenario, thus explicitly taking into account ``model risk''. In this context, we show how to determine the contract parameters conservatively and implement robust risk management strategies. This highlights the necessity of a careful choice of guarantees which are granted to the insurance customer and suggests a new role for a type of ``bonus account'' customary in many life–insurance contracts.
Keywords: G13; G22; 330; Minimum return guarantee; defined-contribution pension plans; life-insurance; uncertain volatility; conservative pricing; robust hedging; Lebensversicherung; Rendite; Garantie; Portfolio-Management; Risikomanagement; Hedging; Optionspreistheorie; Theorie